FACTORS ASSOCIATED WITH ADVERSE PREGNANCY OUTCOMES AMONG HOME AND HEALTH FACILITY DELIVERIES IN LAMU COUNTY, KENYA: A COMPARATIVE CROSS SECTIONAL STUDY (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2018)
Introduction: The burden of adverse perinatal and maternal outcomes is still unacceptably high in low- and  middle-income countries. Although much is known on the risk factors, very little is known about specific  aspects in Lamu County. This is compounded by the fact that the maternal mortality ratio in Lamu almost  doubles the national rate. This study was aimed at providing a framework to assess the probable risk factors  for adverse pregnancy outcomes in the County following both hospital and home deliveries. Methodology: Study design: Comparative cross-sectional study. Setting: Lamu County, both home and hospital deliveries. Study population: Female residents of Lamu County interviewed within a month of data collection, having  delivered in the year 2017 at gestation age of ≥28 weeks and age ≥14 years. Sample size: Using Fleiss formula for comparative cross-sectional study; the sample size was approximated  to be 400 participants after adjusting for attrition. Data collection and management: Data were collected using a questionnaire by trained research assistants,  and entered into an Excel spreadsheet.  Data analysis: Analysis was done using Statistical Package for Social Sciences (SPSS) version 20. Relevant  tests of significance were applied.  Results: The most prevalent adverse obstetric outcomes were post-partum hemorrhage (PPH) requiring  transfusion of at least 2 units of blood and preterm births. PPH was more common following home delivery.  Pre-existing medical conditions, other obstetric emergencies (OR 128.17, CI 14.88 – 110.4, p< 0.001) and  long distance were associated with adverse obstetric outcomes. There was no significant difference in the  prevalence of adverse outcomes between home and hospital deliveries (OR 0.94, C.I 0.55-1.61, p= 0.812).  Conclusion: Multiple factors are associated with adverse obstetric outcomes in Lamu. There is a need to: raise  awareness on the need for greater facility-based skilled birth attendance; build capacity of facilities to provide  comprehensive emergency obstetric care and to train traditional birth attendants to become ambassadors for  early referral.